Wide-distribution easy-to-process polyethylene and application thereof

Through the blending of wide distribution easy-to-process polyethylene and copolymer polypropylene, combined with the dual-kettle parallel process, the problem of light transmittance and haze difference in the production process is solved, and the high fluidity and low cost of the BOPP extinction film are achieved. Production has improved market competitiveness.

CN119192715AActive Publication Date: 2024-12-27ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411269742.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

During the production process, the BOPP extinction film has significant differences in the transmittance and haze between the upper and lower sides and the middle parts due to the difference in tensile ratios between the two sides and the middle parts, resulting in high cost and uneven haze. The existing technology is difficult to effectively solve the problem. This question.

Method used

The wide distribution easy-to-process polyethylene is used, and produced through a dual-kettle parallel process, combining copolymerized polypropylene and antioxidants to improve the fluidity and haze uniformity of the mattress film, reduce the thickness of the mattress layer, and improve the processing rate.

Benefits of technology

The haze errors on the upper and lower sides and middle parts of the single-layer and double-layer extinction film are significantly reduced, which improves the overall extinction effect and production efficiency of the extinction film, reduces costs, and has high water vapor barrier properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192715A_ABST
    Figure CN119192715A_ABST
Patent Text Reader

Abstract

The invention discloses wide-distribution easy-to-process polyethylene and application thereof. The weight-average molecular weight of the wide-distribution easy-to-process polyethylene is 10 * 10 < 4 >-45 * 10 < 4 > g / mol, the molecular weight distribution is 35-50, the content of components with the molecular weight larger than or equal to 100 * 10 < 4 > g / mol is 1-10 wt%, the content of components with the molecular weight smaller than or equal to 1000 g / mol is 0.5-2.5 wt%, the density is 0.940-0.960 g / cm < 3 >, the melt index is 8-15 g / 10 min, the branched chain content is smaller than or equal to 0.2 C / 1000 C, and the tensile strength at break is larger than or equal to 50 MPa. The matting material composed of wide-distribution and easy-to-process polyethylene and polypropylene is applied to a multi-layer co-extrusion casting film and has the characteristics of high haze, small haze deviation and high water vapor barrier property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyolefin material, in particular to a broad distribution easy-to-process polyethylene and its application. Background Art

[0002] BOPP matte film is a special type of biaxially oriented polypropylene (BOPP) film with high haze and low gloss optical properties. This film is made through a special production process, and the surface presents a diffuse reflection matte effect similar to paper, with soft reflected light, giving people a delicate appearance texture. Due to its unique optical and surface properties, BOPP matte film is widely used in various packaging materials, such as food, tobacco, cosmetics, medicines, etc., as well as book, magazine covers and posters.

[0003] The production process of BOPP matte film includes batching, extrusion, casting, biaxial stretching, traction, winding, aging and slitting. During the production process, in order to improve the haze of the film, a certain amount of matte material will be added to the surface of the film. This matte material is usually made by mixing polypropylene and polyethylene in a certain proportion, adding a small amount of plasticizer and antioxidant, and blending and granulating. Compared with polypropylene, the crystallization speed of polyethylene is very fast. Large crystal particles will be formed during the biaxial stretching process, making the surface of the film rough and scattering the light, thus forming a matte effect.

[0004] However, the current BOPP production line has different stretching ratios on both sides and in the middle, resulting in significant differences in transmittance and haze between the upper and lower sides and the middle part of the matte film. The transmittance of the upper and lower sides of the matte film is significantly higher and the haze is lower. In order to eliminate this optical defect, the matte layer on the surface of the matte film is often thickened, resulting in a high overall cost of the matte film and limited profit margins. In addition, the difference in stretching ratios on both sides and in the middle of the film is also partly attributed to the low fluidity of the blended matte material of polyethylene and polypropylene. Invention patent CN111117077A discloses a matte material for BOPP, a preparation method thereof, and a BOPP matte film. The matte material for BOPP includes the following raw materials in weight percentage: copolymerized polypropylene 40%-60%, high-density polyethylene 35%-55%, masterbatch A 5%-15%, and antioxidant masterbatch 0.5%-5%; wherein masterbatch A includes a masterbatch matrix, hydrogenated petroleum resin or rosin resin, and the masterbatch matrix is ​​polypropylene. By adding masterbatch A containing hydrogenated petroleum resin or rosin resin into the formula system, since the melt flow rate of masterbatch A in the molten state is significantly higher than that of copolymerized polypropylene and high-density polyethylene, the overall flow dispersion of the matte material is greatly improved, thereby improving the overall matte uniformity of the BOPP matte film, and improving the problem of uneven matte dispersion on both sides of the existing matte film without thickening the matte layer, thereby improving the overall matte effect of the BOPP matte film and improving the production efficiency.

[0005] Therefore, how to develop a polyethylene resin suitable for blending with polypropylene, taking into account the characteristics of high fluidity, high haze and low haze deviation, and its matte material blended with polypropylene is crucial to thinning the matte layer of the matte film, increasing the processing rate and enhancing the market competitiveness. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a broad distribution easy-to-process polyethylene and its application. The broad distribution easy-to-process polyethylene has the characteristics of excellent processing performance, good fluidity, wide molecular weight distribution and fast crystallization rate.

[0007] According to one object of the present invention, the present invention provides a broad distribution easy-to-process polyethylene, wherein the weight average molecular weight of the broad distribution easy-to-process polyethylene is in the range of 10×10 4 -45×10 4 g / mol, molecular weight distribution is 35-50, molecular weight ≥100×10 4 The content of components with molecular weight ≤1000 g / mol is 1-10wt%, the content of components with molecular weight ≤1000 g / mol is 0.5-2.5wt%, and the density is 0.940-0.960 g / cm 3 , melt index is 8-15g / 10min, branch content is <0.2C / 1000C, and tensile strength at break is ≥50MPa.

[0008] The present invention also provides a method for preparing the broad distribution easy-to-process polyethylene, which comprises:

[0009] In a first reactor, polymer A is dissolved in solvent B, cocatalyst C and catalyst D are added in sequence, α-olefin E and ethylene are introduced to start polymerization reaction, the polymerization temperature is T1, the polymerization time is t, the polymerization pressure is P1, after the polymerization reaction is completed, the slurry in the first reactor is introduced into the product collection tank at a flow rate X1 (the flow rate is based on the weight of the solid phase product); the concentration of polymer A in the first reactor is 0.1-10.0wt%, and the weight average molecular weight of polymer A is ≤1000g / mol;

[0010] At the same time, in the second reactor, solvent B is used as the polymerization medium, the polymerization temperature is T2, the polymerization pressure is P2, and the cocatalyst F, catalyst G, α-olefin H and ethylene are continuously introduced for continuous production, and the slurry in the second reactor is introduced into the product collection tank at a flow rate of X2 (the flow rate is based on the weight of the solid phase product);

[0011] The first reactor and the second reactor are operated in parallel;

[0012] The mixed slurry in the product collection tank is introduced into a solid-liquid separator, the temperature of the solid-liquid separator is T3, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, and extruded and granulated to obtain the broad distribution easy-to-process polyethylene product. The separated liquid phase product can be further refined to obtain solvent B for use in the first reactor and the second reactor.

[0013] According to a preferred embodiment of the present invention, polymer A is selected from one or more of polyethylene wax, oxidized polyethylene wax, polypropylene wax, oxidized polypropylene wax, polybutene, paraffin wax, and Fischer-Tropsch wax.

[0014] According to a preferred embodiment of the present invention, the concentration of polymer A in the first reaction kettle is 0.1-10.0wt%, and solvent B is selected from one or more of n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, methylcyclohexane, 2-methylpentane, 3-methylpentane, n-heptane, 2-methylhexane, 3-methylhexane, n-octane, 2-methylheptane, 3-methylheptane, n-nonane and n-decane; cocatalyst C and cocatalyst F are selected from methylaluminoxane, modified methylaluminoxane, ethylaluminoxane, butylaluminoxane, trimethylaluminum, triethylaluminum, triisobutylamine ... One or more of butylaluminum, trihexylaluminum, trioctylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, tri(2,4,6-trifluorophenyl)borane, and the cocatalyst C and the cocatalyst F may be the same or different; the catalyst D and the catalyst G are selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst, and the catalyst D and the catalyst G may be the same or different;

[0015] The α-olefin E and α-olefin H are selected from one or more of propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene, and the α-olefin E and α-olefin H may be the same or different. The amount of α-olefin E and α-olefin H added is usually selected in accordance with the catalytic activity of the catalyst to ensure that the branch content in the final product is less than 0.2C / 1000C.

[0016] The polymerization temperature T1 is 50-90°C, the polymerization time t is 0.5-10h, and the polymerization pressure P1 is 0.5-2.0MPa.

[0017] According to a preferred embodiment of the present invention, the content of polymer A contained in the solid phase product in the slurry in the first reactor is 0.5-8.0wt%, the weight average molecular weight of polymer A is less than 1000g / mol, and the weight average molecular weight of the solid phase product in the slurry in the first reactor is 80-140×10 4 g / mol, molecular weight distribution is 50-500, branch content is less than 0.2C / 1000C, and the initial elastic modulus of the solid phase product after removing polymer A is 0.2-0.5MPa.

[0018] According to a preferred embodiment of the present invention, polymer A is widely distributed on the surface and inside particles of the solid phase product in the slurry in the first reactor, and the surface of the solid phase product is flaky. Polymer A is distributed between the flaky crystals, and the thickness of the flaky crystals is 10-300nm.

[0019] According to a preferred embodiment of the present invention, the polymerization temperature T2 is 60-100°C, the polymerization pressure P2 is 0.5-2.0 MPa, and the solid-liquid separator temperature T3 is 40-55°C.

[0020] According to a preferred embodiment of the present invention, the ratio of the slurry flow rate X1 in the first reactor to the slurry flow rate X2 in the second reactor is 1:(1.5-9.9), and the polymer A content in the broad distribution easy-to-process polyethylene product is 0.3-2.5wt%. The weight average molecular weight of the solid phase product in the slurry in the second reactor is 10×10 4 -20×10 4 g / mol, molecular weight distribution is 10-30.

[0021] According to a preferred embodiment of the present invention, the high temperature gel chromatography test spectrum of the broad distribution easy-to-process polyethylene product presents an obvious bimodal distribution.

[0022] According to the second object of the present invention, the present invention provides the use of the broad distribution easy-to-process polyethylene in the preparation of matte film.

[0023] According to a preferred embodiment of the present invention, broad distribution easy-to-process polyethylene is mixed with copolymerized polypropylene, a lubricant, and an antioxidant in a weight ratio of 1: (0.8-1.2): (0.02-0.03): (0.001-0.003), and then melt co-extrusion and biaxial stretching are performed to form a surface matte layer of a matte film, wherein the matte film has a three-layer, four-layer, five-layer, six-layer or seven-layer structure. The surface matte layer can be a single layer, or it can exist as both the outer surface layer and the inner surface layer of the matte film (double layer). The haze of the matte film of the single-layer matte layer is ≥80%, and the haze deviation of the upper and lower sides and the middle part of the single-layer matte film is ≤0.3%. The haze of the matte film of the double-layer matte layer is ≥90%, and the haze deviation of the upper and lower sides and the middle part of the double-layer matte film is ≤0.5%. In addition, this matte film also has the advantage of high water vapor barrier properties, with a water vapor permeability of ≤3.5g / (m 2 ·24h).

[0024] Among them, the lubricant is used to improve the slipperiness of the plastic surface, reduce the friction coefficient of the plastic surface, improve the processing performance of the plastic and the performance of the product, and can be oleamide, erucamide, calcium stearate, silicone, low molecular weight polypropylene and other commonly used lubricants in this field; the antioxidant is used to alleviate the automatic oxidation rate of polymer materials, and can be 1010 antioxidant, XX and other commonly used antioxidants in this field.

[0025] The present invention has the following outstanding gain effects:

[0026] (1) The broad distribution easy-to-process polyethylene of the present invention has a wide molecular weight distribution, and the low molecular weight polymer A component can melt quickly and has a strong molecular chain movement ability, which can promote the movement of high molecular weight polyethylene molecular chains around the polymer A molecular chains, so the processing temperature required during the melt processing is lower, and it has better processability and processing economy. After the broad distribution easy-to-process polyethylene is blended with copolymerized polypropylene as a matting material, it has better fluidity during the melt coextrusion and biaxial stretching process, so that the haze error of the upper and lower sides and the middle part of the single-layer matting film and the double-layer matting film is significantly reduced.

[0027] (2) The broad distribution easy-to-process polyethylene of the present invention is produced by a dual-reactor parallel process. The molecular weight distribution of the solid phase product in the first reactor is 50-500, and the initial elastic modulus of the solid phase product after removing polymer A is 0.2-0.5 MPa, which indicates that the solid phase product in the first reactor has the characteristics of low entanglement and broad distribution. The molecular chain movement ability of low-entanglement polyethylene is stronger, and the crystallization rate during melt processing and biaxial stretching is faster, which makes the tensile strength of polyethylene higher. In addition, the weight average molecular weight of the solid phase product in the slurry in the first reactor is 80-140×10 4 g / mol, this low entanglement polyethylene has the characteristics of high molecular weight. According to the knowledge in the field of polymer physics, the higher the molecular weight, the faster the crystallization rate of the molecular chain, which further increases the difference in crystallization rate between polyethylene and polypropylene in the matte material, and the haze of the matte layer and the matte film can be further improved.

[0028] (3) The branch content of the broad distribution and easy-to-process polyethylene of the present invention is less than 0.2C / 1000C, and the branch content of the solid phase product in the slurry in the first reactor is less than 0.2C / 1000C. The lower the branch content, the faster the crystallization rate of the polyethylene molecular chain. This also further increases the difference in crystallization rate between polyethylene and polypropylene in the matte material, and the haze of the matte layer and the matte film can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the elastic modulus G'-time t curve of the solid phase product in the first reaction kettle after removing polymer A at 160°C.

[0030] Figure 2 It is the GPC curve diagram of the solid phase product in the first reactor. DETAILED DESCRIPTION

[0031] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0032] The following methods were used to test the structure or properties of the polyolefins produced in the examples described:

[0033] High temperature gel permeation chromatography (GPC) is used to test the weight average molecular weight and molecular weight distribution of polyethylene.

[0034] Gradient densitometer is used to test the density of polyethylene.

[0035] The melt index meter is used to test the melt index of polyethylene.

[0036] Analytical temperature rising elution fractionation (TREF) is used to measure the short chain branch content of polyethylene.

[0037] Universal testing machine is used to test the tensile strength of polyethylene.

[0038] The polymer A content in the polyethylene product was separated by heating and eluting with xylene and the mass content was calculated by weighing.

[0039] Rotational rheometer is used to test the initial elastic modulus of polyethylene.

[0040] The haze meter is used to test the haze of the film.

[0041] Thickness gauge is used to test the thickness of the film.

[0042] Water vapor transmission rate tester is used to test the water vapor transmission rate of films.

[0043] Example 1

[0044] 120 kg of Fischer-Tropsch wax (weight average molecular weight 650 g / mol) was dissolved in the first reaction kettle (medium hexane, volume 10 m 3 ), 1.3L triethylaluminum, 12g Ziegler-Natta catalyst, 40L 1-hexene were added in sequence, ethylene was introduced to start polymerization, the polymerization temperature was 57°C, the polymerization time (residence time) was 3.3h, and the polymerization pressure was 1.0MPa; the second reactor (volume 40m 3) with hexane as polymerization medium, polymerization temperature of 88°C, polymerization pressure of 1.3MPa, continuously introducing triethylaluminum, Ziegler-Natta catalyst, 1-hexene and ethylene for continuous production; the first reactor and the second reactor are produced in parallel, the slurry in the first reactor is introduced into the product collection tank at 1t / h, and the slurry in the second reactor is introduced into the product collection tank at 6.5t / h. The mixed slurry in the product collection tank is introduced into the solid-liquid separator, the temperature of the solid-liquid separator is 45°C, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain a broad distribution easy-to-process polyethylene product a. The analysis and characterization results of product a are shown in Table 1.

[0045] Example 2

[0046] 125 kg of microcrystalline wax (weight average molecular weight 800 g / mol) was dissolved in the first reaction kettle (medium cyclohexane, volume 10 m 3 ), 1.2L triisobutylaluminum, 18g Ziegler-Natta catalyst, 60L 1-hexene were added in sequence, ethylene was introduced to start polymerization, the polymerization temperature was 63°C, the polymerization time (residence time) was 3h, and the polymerization pressure was 0.9MPa; the second reactor (volume 40m 3 ) with cyclohexane as polymerization medium, polymerization temperature of 84°C, polymerization pressure of 1.8MPa, continuously introducing triisobutylaluminum, Ziegler-Natta catalyst, 1-hexene and ethylene for continuous production; the first reactor and the second reactor are produced in parallel, the slurry in the first reactor is introduced into the product collection tank at 1.1t / h, and the slurry in the second reactor is introduced into the product collection tank at 5.9t / h. The mixed slurry in the product collection tank is introduced into the solid-liquid separator, the temperature of the solid-liquid separator is 51°C, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain a broad distribution easy-to-process polyethylene product b. The analysis and characterization results of product b are shown in Table 1.

[0047] Example 3

[0048] 100 kg paraffin (weight average molecular weight 500 g / mol) was dissolved in the first reaction kettle (medium cyclohexane, volume 10 m 3 ), 1.2L modified methylaluminoxane, 15g supported metallocene catalyst, 20L 1-hexene, 40L 1-octene were added in sequence, ethylene was introduced to start polymerization, the polymerization temperature was 73°C, the polymerization time (residence time) was 2.1h, and the polymerization pressure was 1.5MPa; the second reactor (volume 40m 3) with cyclohexane as polymerization medium, polymerization temperature of 82°C, polymerization pressure of 1.3MPa, continuously introducing modified methylaluminoxane, supported metallocene catalyst, 1-hexene and ethylene for continuous production; the first reactor and the second reactor are produced in parallel, the slurry in the first reactor is introduced into the product collection tank at 0.9t / h, and the slurry in the second reactor is introduced into the product collection tank at 3.9t / h. The mixed slurry in the product collection tank is introduced into the solid-liquid separator, the temperature of the solid-liquid separator is 54°C, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain a broad distribution easy-to-process polyethylene product c. The analysis and characterization results of product c are shown in Table 1.

[0049] Example 4

[0050] 200 kg of polyethylene wax (weight average molecular weight 800 g / mol) was dissolved in the first reaction kettle at a concentration of 4.0 wt% (medium: n-hexane, volume 10 m 3 ), 0.8L triethylaluminum, 14g Ziegler-Natta catalyst, 80L 1-hexene were added in sequence, ethylene was introduced to start polymerization, the polymerization temperature was 74°C, the polymerization time (residence time) was 4.2h, and the polymerization pressure was 0.9MPa; the second reactor (volume 40m 3 ) with n-hexane as polymerization medium, polymerization temperature of 84°C, polymerization pressure of 1.4MPa, continuously introducing triethylaluminum, supported metallocene catalyst, 1-hexene and ethylene for continuous production; the first reactor and the second reactor are produced in parallel, the slurry in the first reactor is introduced into the product collection tank at 1.4t / h, and the slurry in the second reactor is introduced into the product collection tank at 5.6t / h. The mixed slurry in the product collection tank is introduced into the solid-liquid separator, the temperature of the solid-liquid separator is 42°C, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain a broad distribution easy-to-process polyethylene product d. The analysis and characterization results of product d are shown in Table 1.

[0051] Comparative Example 1

[0052] The first reactor (volume 10m 3 ) with n-hexane as polymerization medium, 1.0L triethylaluminum, 13g Ziegler-Natta catalyst, 40L 1-hexene were added in sequence, ethylene was introduced to start polymerization, the polymerization temperature was 67°C, the polymerization time (residence time) was 4.3h, and the polymerization pressure was 0.7MPa; the second reactor (volume 40m 3) with n-hexane as polymerization medium, polymerization temperature of 87°C, polymerization pressure of 1.2MPa, continuously introducing triethylaluminum, Ziegler-Natta catalyst, 1-hexene and ethylene for continuous production; the first reactor and the second reactor are produced in parallel, the slurry in the first reactor is introduced into the product collection tank at 1.3t / h, and the slurry in the second reactor is introduced into the product collection tank at 5.6t / h. The mixed slurry in the product collection tank is introduced into the solid-liquid separator, the temperature of the solid-liquid separator is 43°C, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain polyethylene product e. The analysis and characterization results of product e are shown in Table 1.

[0053] Table 1 Polyethylene ae characterization results

[0054]

[0055]

[0056] As shown in Table 1 above, the polyethylene products ad of Examples 1-4 have higher melt index, wider molecular weight distribution, and higher tensile strength at break than the polyethylene product e in Comparative Example 1, which indicates that the polyethylene products ad have better processability and mechanical properties. In addition, the content of polymer A in the polyethylene products ad is higher, and the initial elastic modulus of the solid phase product in the first reactor after removing polymer A is lower (0.27-0.38 MPa, see Appendix Figure 1 ), the molecular weight distribution of the solid phase product in the first reactor is very wide (see Appendix Figure 2 ), and the surface of the solid phase product in the first reactor after polymer A is removed is scaly. Polymer A is not contained in polyethylene product e, and the initial elastic modulus of the solid phase product in the first reactor is as high as 0.83MPa, and there is no obvious scaly lamella structure on the surface of the solid phase product. The above results show that the molecular chain of polyethylene product e is highly entangled. Affected by the entanglement point, the molecular chain is difficult to open quickly, the molecular chain has weak mobility, and it is difficult to crystallize quickly during melt processing and biaxial stretching. This results in a low melt index of polyethylene product e, greater processing difficulty, and reduced economic efficiency of the processing process.

[0057] Example 5

[0058] 100 parts of the polyethylene product a in Example 1, 100 parts of polypropylene (melting 10.5 g / 10 min), 2 parts of a lubricant and 0.2 parts of a commercially available 1010 antioxidant were mixed in a high-speed mixer for 3 min, then melt-extruded and granulated in a twin-screw extruder and dried at a granulation temperature of 235°C to obtain a matte material A.

[0059] The matte material A was cast into film in a three-layer co-extrusion casting device at a ratio of 100 parts, 500 parts of the middle layer raw material, and 200 parts of the inner surface layer raw material. The extruder temperature was 240°C, the die temperature was 235°C, the longitudinal stretching temperature after film formation was 125°C, the setting temperature was 130°C, the transverse stretching temperature was 155°C, the setting temperature was 166°C, the longitudinal stretching was 4.8 times, and the transverse stretching was 8 times to obtain matte film A. The characterization results of matte film A are shown in Table 2.

[0060] Example 6

[0061] 100 parts of the polyethylene product B in Example 2, 90 parts of polypropylene (melting 10.5 g / 10 min), 2 parts of a lubricant and 0.1 parts of a commercially available 1010 antioxidant were mixed in a high-speed mixer for 3 min, then melt-extruded and granulated in a twin-screw extruder and dried at a granulation temperature of 240°C to obtain a matte material B.

[0062] The matting material B was 100 parts, the intermediate layer raw material was 550 parts, and the inner surface layer raw material was 200 parts, and the film was cast in a three-layer co-extrusion casting device, the extruder temperature was 240°C, the die temperature was 236°C, the longitudinal stretching temperature after film formation was 126°C, the setting temperature was 131°C, the transverse stretching temperature was 155°C, the setting temperature was 167°C, the longitudinal stretching was 4.8 times, and the transverse stretching was 8 times to obtain the matting film B. The characterization results of the matting film B are shown in Table 2.

[0063] Example 7

[0064] 100 parts of the polyethylene product C in Example 3, 110 parts of polypropylene (melting 11.5 g / 10 min), 3 parts of a lubricant and 0.3 parts of a commercially available 1010 antioxidant were mixed in a high-speed mixer for 3 min, then melt-extruded and granulated in a twin-screw extruder and dried at a granulation temperature of 240°C to obtain a matte material C.

[0065] Matt material C 110 parts, middle layer raw material 600 parts, inner surface layer raw material 220 parts, cast into film in a three-layer co-extrusion casting device, extruder temperature 240 ° C, die head temperature 235 ° C, longitudinal stretching temperature 125 ° C, shaping temperature 130 ° C, transverse stretching temperature 155 ° C, shaping temperature 166 ° C, longitudinal stretching 4.8 times, transverse stretching 8 times, to obtain matt film C. The characterization results of matt film C are shown in Table 2.

[0066] Example 8

[0067] 100 parts of the polyethylene product d in Example 4, 1150 parts of polypropylene (melting 10.3 g / 10 min), 3 parts of a lubricant and 0.3 parts of a commercially available 1010 antioxidant were mixed in a high-speed mixer for 3 min, then melt-extruded and granulated in a twin-screw extruder and dried at a granulation temperature of 238°C to obtain a matte material D.

[0068] The matte material D was cast into film in a three-layer co-extrusion casting device at a ratio of 100 parts, 650 parts of the intermediate layer raw material, and 200 parts of the inner surface layer raw material. The extruder temperature was 240°C, the die temperature was 235°C, the longitudinal stretching temperature after film formation was 125°C, the setting temperature was 130°C, the transverse stretching temperature was 155°C, the setting temperature was 166°C, the longitudinal stretching was 4.8 times, and the transverse stretching was 8 times to obtain a matte film D. The characterization results of the matte film D are shown in Table 2.

[0069] Comparative Example 2

[0070] 100 parts of the polyethylene product e in Comparative Example 1, 100 parts of polypropylene (melting 10.5 g / 10 min), 2 parts of a lubricant and 0.3 parts of a commercially available 1010 antioxidant were mixed in a high-speed mixer for 3 min, then melt-extruded and granulated in a twin-screw extruder and dried at a granulation temperature of 238°C to obtain matte E.

[0071] The matte material E was 100 parts, the intermediate layer raw material was 520 parts, and the inner surface layer raw material was 200 parts, and the film was cast in a three-layer co-extrusion casting device, the extruder temperature was 240°C, the die temperature was 235°C, the longitudinal stretching temperature after film formation was 125°C, the setting temperature was 130°C, the transverse stretching temperature was 155°C, the setting temperature was 166°C, the longitudinal stretching was 4.8 times, and the transverse stretching was 8 times to obtain the matte film E. The characterization results of the matte film E are shown in Table 2.

[0072] Table 2 AE characterization results of matt film

[0073]

[0074] As shown in Table 2 above, the matte films AD of Examples 5-8 have higher haze than the matte film E in Comparative Example 2, and the deviation value of the haze (maximum value minus minimum value) is not higher than 0.2%. This is mainly because the molecular chain mobility of the polyethylene in the matte material AD is stronger, and the crystallization ability of the polyethylene molecular chain is enhanced, which widens the difference in crystallization rate between the polyethylene and polypropylene molecular chains, increases the concavo-convexity of the surface of the matte layer of the matte film, and leads to enhanced diffuse reflection behavior of light and increased haze. And because the polyethylene ad in the matte material AD has better fluidity, the haze error of the upper and lower sides and the middle part of the matte film is significantly reduced. In addition, the water vapor barrier performance of the matte film AD is excellent, and its water vapor transmittance is lower than 3.3g / (m 2 ·24h), significantly lower than the 6.82g / (m 2 ·24h).

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A broad distribution easy-to-process polyethylene, characterized in that: The weight average molecular weight of the broad distribution easy-to-process polyethylene is in the range of 10×10 4 -45×10 4 g / mol, molecular weight distribution is 35-50, molecular weight ≥100×10 4 The content of components with molecular weight ≤1000 g / mol is 1-10wt%, the content of components with molecular weight ≤1000 g / mol is 0.5-2.5wt%, and the density is 0.940-0.960 g / cm 3 , melt index is 8-15g / 10min, branch content is <0.2C / 1000C, and tensile strength at break is ≥50MPa.

2. The broad distribution easy-to-process polyethylene according to claim 1, characterized in that: The broad distribution easy-to-process polyethylene is prepared by the following steps: In the first reactor, polymer A is dissolved in solvent B, cocatalyst C and catalyst D are added in sequence, α-olefin E and ethylene are introduced to start polymerization reaction, the polymerization temperature is T1, the polymerization time is t, the polymerization pressure is P1, after the polymerization reaction is completed, the slurry in the first reactor is introduced into the product collection tank at a flow rate of X1; the concentration of polymer A in the first reactor is 0.1-10.0wt%, and the weight average molecular weight of polymer A is ≤1000g / mol; At the same time, in the second reactor, solvent B is used as the polymerization medium, the polymerization temperature is T2, the polymerization pressure is P2, and the cocatalyst F, catalyst G, α-olefin H and ethylene are continuously introduced for continuous production, and the slurry in the second reactor is introduced into the product collection tank at a flow rate of X2; The first reactor and the second reactor are operated in parallel; The mixed slurry in the product collection tank is introduced into a solid-liquid separator, the temperature of the solid-liquid separator is T3, and the solid phase product separated by the solid-liquid separator is dried, devolatilized, extruded and granulated to obtain the broad distribution easy-to-process polyethylene product.

3. The broad distribution easy-to-process polyethylene according to claim 2, characterized in that: The polymer A is selected from one or more of polyethylene wax, oxidized polyethylene wax, polypropylene wax, oxidized polypropylene wax, polybutene, paraffin wax, and Fischer-Tropsch wax.

4. The broad distribution easy-to-process polyethylene according to claim 2, characterized in that: Solvent B is selected from one or more of n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, methylcyclohexane, 2-methylpentane, 3-methylpentane, n-heptane, 2-methylhexane, 3-methylhexane, n-octane, 2-methylheptane, 3-methylheptane, n-nonane and n-decane; The cocatalyst C and the cocatalyst F are selected from one or more of methylaluminoxane, modified methylaluminoxane, ethylaluminoxane, butylaluminoxane, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane, and the cocatalyst C and the cocatalyst F may be the same or different; Catalyst D and catalyst G are selected from one or more of metallocene catalysts, late transition metal catalysts, Ziegler-Natta catalysts, non-metallocene catalysts, and FI catalysts, and catalyst D and catalyst G may be the same or different; α-olefin E and α-olefin H are selected from one or more of propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene, and α-olefin E and α-olefin H may be the same or different; The polymerization temperature T1 is 50-90°C, the polymerization time t is 0.5-10h, and the polymerization pressure P1 is 0.5-2.0MPa.

5. The broad distribution easy-to-process polyethylene according to claim 1, characterized in that: The solid phase product in the slurry in the first reaction kettle contains a polymer A content of 0.5-8.0 wt %, and the weight average molecular weight of the solid phase product in the slurry in the first reaction kettle is 80-140×10 4 g / mol, molecular weight distribution is 50-500, branch content is ≤0.2C / 1000C, and the initial elastic modulus of the solid phase product after removing polymer A is 0.2-0.5MPa.

6. The broad distribution easy-to-process polyethylene according to claim 5, characterized in that: The polymer A is distributed on the surface and inside the particles of the solid phase product in the slurry in the first reaction kettle, and the surface of the solid phase product is flaky. The polymer A is distributed between the flaky crystals, and the thickness of the flaky crystals is 10-300nm.

7. The broad distribution easy-to-process polyethylene according to claim 2, characterized in that: The polymerization temperature T2 is 60-100°C, the polymerization pressure P2 is 0.5-2.0MPa, and the solid-liquid separator temperature T3 is 40-55°C.

8. The broad distribution easy-to-process polyethylene according to claim 2, characterized in that: The flow rate X1 and the flow rate X2 are both measured by weight of the solid phase product, the ratio of the slurry flow rate X1 in the first reactor to the slurry flow rate X2 in the second reactor is 1:(1.5-9.9), and the polymer A content in the broad distribution easy-to-process polyethylene product is 0.3-2.5wt%; the weight average molecular weight of the solid phase product in the slurry in the second reactor is 10×10 4 -20×10 4 g / mol, molecular weight distribution is 10-30.

9. Use of the broad distribution easy-to-process polyethylene according to any one of claims 1 to 8 in the preparation of matte films.

10. The use according to claim 9, characterized in that: The broad distribution easy-to-process polyethylene is mixed with polypropylene, a lubricant and an antioxidant in a weight ratio of 1:(0.8-1.2):(0.02-0.03):(0.001-0.003), and then the mixture is used as a surface matte layer of a matte film by melt coextrusion and biaxial stretching. The matte film has a three-layer, four-layer, five-layer, six-layer or seven-layer structure. The surface matte layer can be a single layer, or it can exist as both the outer surface layer and the inner surface layer of the matte film. The haze of the matte film of the single-layer matte layer is ≥80%, and the haze deviation of the upper and lower sides and the middle part of the single-layer matte film is ≤0.3%. The haze of the matte film of the double-layer matte layer is ≥90%, and the haze deviation of the upper and lower sides and the middle part of the double-layer matte film is ≤0.5%. The water vapor barrier rate of the matte film is ≤3.5g / (m 2 ·24h).

Citation Information

Patent Citations

  • Polyolefin in-situ blend and preparation method and application thereof

    CN116948288A

  • High-wear-resistance polyethylene composite particle as well as material and application thereof

    CN116948296A